PERANCANGAN PIPELINE FOTOGRAMETRI PADA PROSES REVERSE ENGINEERING MODEL TIGA DIMENSI DI PT PRESA GENTA ENGINEERING - Farhan Dewanto, Muhammad
PT Presa Genta Engineering (PGE) is a manufacturing company that implements an engineer-to-order (ETO) system. The company faces issues in the reverse engineering process, which is time-consuming and has inconsistent accuracy. This research aims to apply photogrammetry techniques in the reverse engineering process of three-dimensional models of PT PGE's products as an alternative method for conducting the process. Photogrammetry was chosen as a solution to overcome the limitations of manual methods in measuring and creating computer-aided designs of three-dimensional products.